Korelasi Radiologis-Patologis pada Adenokarsinoma Paru: Tinjauan Sistematis - Nanda Robby Setyawan (Jurnal Medika Nusantara, 2026)
Lung adenocarcinoma is the most common histological subtype of lung cancer and demonstrates substantial heterogeneity in both radiological and pathological features, posing challenges in noninvasive assessment of tumor invasiveness. Computed tomography (CT) plays a central role in the evaluation of pulmonary lesions; however, the correlation between radiological characteristics and pathological findings in lung adenocarcinoma requires systematic evaluation. This study aimed to analyze radiologic–pathologic correlations in lung adenocarcinoma and to assess the potential of CT imaging features in predicting tumor invasiveness. A systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, including observational studies and clinical trials published within the last decade. Literature searches were performed using PubMed, ScienceDirect, and SpringerLink databases, yielding ten retrospective studies that met the inclusion criteria and were analyzed descriptively. The results demonstrated that ground-glass opacity was the predominant radiological feature of lung adenocarcinoma, while an increased proportion of solid components was consistently associated with higher pathological invasiveness. Additional CT features correlated with invasive adenocarcinoma included larger lesion size, irregular margins, lobulation, air bronchogram, vascular invasion, and pleural tags. A higher proportion of ground-glass opacity was also associated with the presence of epidermal growth factor receptor mutations. In conclusion, CT imaging shows a meaningful correlation with pathological findings and serves as a valuable noninvasive tool for early risk stratification of lung adenocarcinoma; however, it cannot replace histopathological examination as the diagnostic gold standard.